Kill fee - Laukkanen, Owen, 1983- (Stevens & Windermere, 2015)
The billionaire picked a heck of a way to die.On a beautiful Saturday in downtown Saint Paul, Minnesota, state investigator Kirk Stevens and his occasional colleague FBI special agent Carla Windermere witness the assassination of one of the state's wealthiest men.The shooter is a young man, utterly unremarkable-except in his eyes.There is something very wrong in his eyes.And it's only the beginning.The events of that sunny springtime day will lead Stevens and Windermere across the country, down countless blind alleys, and finally to a very flourishing twenty-first-century enterprise:a high-tech murder-for-hire social media website.But just who has the dead-eyed shooter targeted next . . .and who's choosing his victims?That's where things get complicated.